The Effect of the PBL Model to Increase Student Learning Activities in Integrated Thematic Learning in Elementary Schools - Daniel Pasaribu; Lince Marwiyah Tanjung; Rame Yantina; Tri Utami; Laurensia M. Perangin Angin (Journal of Educational Analytics, 2023)
The facts show that the low involvement of students in integrated thematic learning is due to the lack of a suitable model used in learning. The research aims to increase student learning activities using the PBL model. This is classroom action research, carried out in the stages of planning, implementing, observing, and reflecting. The research approach is both qualitative and quantitative. The results of the study show that the use of the PBL model in integrated thematic learning can increase student learning activities, and students are able to work together with their group members, which ultimately leads to an increase in student learning abilities in integrated thematic subjects. The results showed an increase in student learning activity from 63% in cycle I to 93% in cycle II. It was concluded that the use of the PBL model was very effective in increasing student learning activities.